Characterizing crosstalk in epigenetic signaling to understand disease physiology. Issue 1 (13th January 2023) - Lempiäinen, Joanna K.; Garcia, Benjamin A.
Abstract : Epigenetics, the inheritance of genomic information independent of DNA sequence, controls the interpretation of extracellular and intracellular signals in cell homeostasis, proliferation and differentiation. On the chromatin level, signal transduction leads to changes in epigenetic marks, such as histone post-translational modifications (PTMs), DNA methylation and chromatin accessibility to regulate gene expression. Crosstalk between different epigenetic mechanisms, such as that between histone PTMs and DNA methylation, leads to an intricate network of chromatin-binding proteins where pre-existing epigenetic marks promote or inhibit the writing of new marks. The recent technical advances in mass spectrometry (MS) -based proteomic methods and in genome-wide DNA sequencing approaches have broadened our understanding of epigenetic networks greatly. However, further development and wider application of these methods is vital in developing treatments for disorders and pathologies that are driven by epigenetic dysregulation.